Role of Biomarkers in Guiding Cure of Viral Hepatitis B - Buti, Maria; Riveiro-Barciela, Mar; Rodríguez-Frías, Francisco; Tabernero, David; Esteban, Rafael (Seminars in Liver Disease, 2020)
Chronic hepatitis B (CHB) virus infection is a global public health threat affecting approximately 257 million individuals worldwide. Hepatitis B surface antigen (HBsAg) loss has been the classic endpoint to define functional cure and decrease the large pool of individuals with CHB. Current treatments with nucleos(t)ide analogues persistently suppress hepatitis B virus (HBV) deoxyribonucleic acid in most CHB patients, but rarely achieve functional cure. New viral biomarkers, such as quantitative HBsAg, hepatitis B core-related antigen, and HBV ribonucleic acid, and combinations of these markers have the potential role of guiding HBV cure by enabling selection of the best candidates for therapy, identifying individuals with a higher likelihood of achieving HBsAg loss, and helping in the design of studies with new drugs. However, some of the assays used to analyze these markers require standardization and improvements in the level of detection. Analysis of host biomarkers to assess the host immune response to HBV is also important, as the natural course of CHB is determined by the interplay between viral replication and the immune response. These biomarkers are, however, in an early phase of development.
Keywords: hepatitis B virus; pregenomic RNA; HBcrAg; quantitative HBsAg; functional cure